Pluralisms? Social philosophy, social science and public policy in employment relations and human resource management. (April 2021) - Ackers, Peter
Alan Fox's frames of reference has sparked over half a century of debate between employment relations/human resource management pluralists, radicals and unitarists. But the notion of industrial relations pluralism itself continues to be highly disputed. This commentary tracks the journey from classical pluralism to neo-pluralism, then addresses three articles that offer a variety of radical pluralist alternatives. A fourth paper discussed, suggests a quantitative approach to testing Fox's frames, but this article makes a case for retaining the qualitative, case study method. A fifth explores the revival of paternalism on the border between unitarism and pluralism. Overall, the article argues that classical pluralism, based on trade unions and collective bargaining, is now outdated, but that neo-pluralism is capable of carrying forward its pragmatic, institutional spirit to explore the empirical complexity of contemporary employment relationships around the world. Finally, the discussion of employment relations pluralisms needs to re-engage with the wider political pluralism debate about liberal democratic societies and market economies.